Bildmittenübersicht/Index Map 1:500 000 Vestfjella, Antarktisepeditionen 1985/86, 1986/87 - Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie); Frankfurt am Main (Institut für Angewandte Geodäsie (Now: Bundesamt für Kartographie und Geodäsie), Frankfurt am Main, 1988)
Flight index map of vertical aerial photography, 1985/86 and 1986/87 expeditions (Topographic background: Satellite imagery); Accuracy referred to geographic graticule only approximated; Photographic material, Aerial photo scale and Flight dates, see map legend; Inset maps: Location diagram Scale: 1:500000; Projection: Not Given; Bounding Box: POLYGON ((-6 -71.2, 2 -71.2, 2.25 -74.333, -7 -74.333, -6 -71.2))